Clinical Outcome Predictor using Killip Scoring in Acute Decompensated Heart Failure (ADHF): A Non-Cardiac Centre Pilot Experience - Ling, Hwei Sung; Chung, Joshua Bui Khiong; Chua, Pin Fen; Gan, Kai Xin; Ong, Elora Yoke Ling; How, Wai Lenga; Kueh, Cindy Hui San; Chin, Yie Ping; Fong, Alan Yean Yip (Elsevier, 2018)
Background: Physicians in tertiary centers face a constant challenge in selecting patient with ADHF to be admitted from district healthcare centre, especially with limited resources. Appropriate risk stratification of patients with ADHF would improve the efficiency of our healthcare delivery system.